2013
DOI: 10.1021/la402287a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of Low Fouling Zwitterionic Polymer Brushes in Seawater with Diblock Architecture

Abstract: The successful implementation of zwitterionic polymeric brushes as antifouling materials for marine applications is conditioned by the stability of the polymer chain and the brush-anchoring segment in seawater. Here we demonstrate that robust, antifouling, hydrophilic polysulfobetaine-based brushes with diblock architecture can be fabricated by atom-transfer radical polymerization (ATRP) using initiator-modified surfaces. Sequential living-type polymerization of hydrophobic styrene or methyl methacrylate and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 56 publications
5
90
2
Order By: Relevance
“…Interestingly, positively charged, [75][76][77] properties that should also be interesting for dental applications. Additionally, these polymers are able to interact with solids.…”
mentioning
confidence: 99%
“…Interestingly, positively charged, [75][76][77] properties that should also be interesting for dental applications. Additionally, these polymers are able to interact with solids.…”
mentioning
confidence: 99%
“…The resulting mixture was stirred until homogenization and then was transferred by cannula into a customized reactor containing the CMPS-modified silicon substrates. The reactor was placed in an oil bath at 25°C and the reaction was continued for 12 h. Then, the substrates were removed from the reactor and rinsed several times with warm water and methanol, and finally rinsed with abundant water and dried under a stream of argon [6,7].…”
Section: Conventional Mediummentioning
confidence: 99%
“…Zwitterionic species such as sulfobetaine methacrylate (SBMA) and sulfobetainemethacrylamide (SBMAm) grafted polymer brushes have shown excellent antifouling properties [1,[6][7][8][9][10]. The presence of zwitterions in the polymer led to the overall electrical neutrality and a dehydrated state [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the low friction is attributed to the hydration lubrication mechanism arising from rubbing of the highly hydrated phosphocholine-head group layers exposed at the outer surface of each liposome, and provides support for the conjecture that phospholipids may play a significant role in biological lubrication [104]. Quintana et al reported some low fouling zwitterionic polymer brushes with diblock architecture which can enhance the stability in seawater [105]. Hydrophilic polymer brushes can also improve the wettability and antifouling behaviour of the surfaces [106].…”
Section: Current State-of-the-art In Brush Coatings and Applicationsmentioning
confidence: 86%